THE ROLE OF COMMUNICATION TO THE DIFFERENCES OF FARMER COMMUNITIES IN KEMIREN VILLAGE KECAMATAN GLAGAH BANYUWANGI DISTRICT - Dinna Lestari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
Agricultural development that have been conducted so far, on the one hand have managed to change the face of agriculture in Indonesia is no exception in the village Kemiren. The origin of the word itself Kemiren according to village elders, village Kemiren ago when first discovered, the village is still forested and there are lots of pecan trees and durian (durian) so that from then on, the area is called